Analisis Kualitas Sumber Mata Air dengan Metode Storet di Desa Manisharjo Kecamatan Ngrambe Kabupaten Ngawi Jawa Timur - Mahmud Dwi Wardoyo; Faradlillah Saves (Portal: Jurnal Teknik Sipil, 2026)
Abstract — Spring water, as part of groundwater resources, is widely utilized by communities for daily needs; therefore, its quality must comply with health standards. This study aims to assess the quality of spring water in Manisharjo Village, Ngrambe District, Ngawi Regency based on physical, chemical, and biological parameters and to determine water quality status using the STORET method. Samples were collected from three spring water sources that are still used by local residents. In-situ measurements were conducted for temperature, odor, taste, pH, and TDS, while ex-situ laboratory analyses were performed for hardness, detergent content, and Escherichia coli. The results were compared with Indonesian Ministry of Health Regulation No. 32 of 2017. STORET analysis shows that spring water source 1 obtained a score of -1 with a good to lightly polluted category, while sources 2 and 3 obtained scores of -14 and -17, both classified as lightly polluted. Overall, the decline in water quality is influenced by chemical and biological parameters that exceed allowable standards.